The server is dead, long live the server: The Rise of Serverless Computing. - CASTRO, PAUL; ISHAKIAN, VATCHE; MUTHUSAMY, VINOD; SLOMINSKI, ALEKSANDER (Communications of the ACM, 2019)
The article discusses the advantages of the concept of what the article terms serverless computing, particularly relating to the release of cloud computing applications. According to the article, high technology firms such as Amazon, Google, and Microsoft have unleashed various serverless capabilities. The article examines the cost of serverless computing, the architecture of serverless computing, and programming models. It mentions Mobile Backend as-a-Service (MBaaS).